Effectiveness of Scaffolding Strategies in Learning Against Decrease in Mathematics Anxiety Level - Imam Kusmaryono; Akbar Muntoha Gufron; Achmad Rusdiantoro (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This study is a mixture of quantitative and qualitative with sequential explanatory designs. The study aims to (1) analyze the improvement of student achievement in learning after scaffolding, (2) evaluate the level of students 'mathematics anxiety, and (3) describe the role of scaffolding in changing students' perceptions of mathematics anxiety in classroom learning. Sampling through random sampling techniques obtained by students of class X-IPA-1 and X-IPA-2 in SMA Negeri 6 Semarang. Quantitative data analysis uses statistical test techniques: normality test, paired sample t-test, and N-gain test. Qualitative data analysis through interactive methods namely data collection, data reduction, data presentation, and drawing conclusions. Data validation techniques through the source and method triangulation. The results showed that (1) there was an increase in student learning achievement after the application of the scaffolding strategy by 33.0% to 34.5%; (2) there was a decrease in the level of mathematics anxiety in students by 90.4%; (3) through scaffolding, students succeed in reflecting and correcting mistakes in solving previous problems. This means scaffolding can be an effective strategy to help students move across different Zones of Proximal Development (ZPD). The scaffolding strategy has also created a positive classroom environment that encourages students to learn mathematics without fear.